2011
DOI: 10.1002/esp.2170
|View full text |Cite
|
Sign up to set email alerts
|

Comments to Westaway and Bridgland – ‘Causes, consequences and chronology of large‐magnitude palaeoflows in Middle and Late Pleistocene river systems of northwest Europe’

Abstract: Westaway and Bridgland (Earth Surface Processes and Landforms 35: 1071-1094, 2010) discuss the causes, the consequences and the chronology of large-magnitude palaeoflows in Pleistocene river systems of northwest Europe. Based on their calculations, these authors suggest that the combined effects of meltwater from Alpine glaciers, rainfall, snowmelt and melting of permafrost during Heinrich Events (HEs) explain the large-magnitude discharges of the Fleuve Manche palaeoriver which punctuated the last glacial per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 31 publications
(87 reference statements)
1
18
0
Order By: Relevance
“…Much of the Toucanne et al () critique concerns a single paragraph in our paper, tentatively suggesting how the chronologies of sediments deposited by affluents of the Channel River, of de‐glaciation, and of marine deposition in the Bay of Biscay in the latter part of the Late Pleistocene may have been interrelated. They accuse Westaway and Bridgland () of ‘misuse’ of papers produced by their team at IFREMER.…”
Section: Differences In Chronologymentioning
confidence: 70%
See 4 more Smart Citations
“…Much of the Toucanne et al () critique concerns a single paragraph in our paper, tentatively suggesting how the chronologies of sediments deposited by affluents of the Channel River, of de‐glaciation, and of marine deposition in the Bay of Biscay in the latter part of the Late Pleistocene may have been interrelated. They accuse Westaway and Bridgland () of ‘misuse’ of papers produced by their team at IFREMER.…”
Section: Differences In Chronologymentioning
confidence: 70%
“…Toucanne et al () placed this event during 18·3−17 ka, whereas Toucanne et al () placed it between 18·3 ka and either 17·5 or 17 ka, depending on which marine borehole dataset was examined. Toucanne et al () now say that it was during 18·3−17·5 ka. However, when analysing another borehole dataset, Auffret et al () reported the two most recent peaks in sediment flux, which must now be regarded as derived from the Channel River (but see also later), at 23·7 and 16·7 ka.…”
Section: Differences In Chronologymentioning
confidence: 99%
See 3 more Smart Citations